Can Differences in Symbiont Transmission Mode Explain the Abundance and Distribution of Fungus-Growing Termites in West Africa? - Korb, Judith; Silué, Simon Kolotchèlèma; Koné, N'golo Abdoulaye (Frontiers in Ecology and Evolution, 2020)
Fungus-growing termites (Isoptera: Macrotermitinae) dominate African savannah ecosystems where they play important roles in ecosystem functioning. Their ecological dominance in these ecosystems has been attributed to living in an ectosymbiosis with fungi of the genus Termitomyces (Lyophyllaceae). Evolutionary theory predicts that the transmission mode of a symbiont determines cooperation and conflict between host and symbiont with vertical transmission (co-transmission of host and symbiont offspring to the next generation) leading to less conflict than horizontal transmission (symbionts are acquired by the host from the environment). Thus, one can hypothesize associations with vertical transmission to be ecological more successful than those with horizontal transmission. We tested this by analysing whether there is an association between transmission mode and fungus-growing termite species abundance and distribution in West-African savannah and forest ecosystems. We used data from a total of 78 study sites comprising protected National Parks as well as anthropogenically disturbed ecosystems, covering Benin, Côte d’Ivoire, and Togo. Our results showed that, in contrast to expectation, species with horizontal symbiont transmission were more common. We encountered more often species with horizontal than vertical transmission. This result might be due to the fact that only five out of the 25 identified fungus-growing termite species had vertical transmission. Yet, species with horizontal transmission also had higher relative abundances within study sites than those with vertical transmission. Thus transmission mode is unlikely to explain abundance differences between fungus-growing termite species.